Optique: Zooming in on Big Data. - Giese, Martin; Soylu, Ahmet; Vega-Gorgojo, Guillermo; Waaler, Arild; Haase, Peter; Jimenez-Ruiz, Ernesto; Lanti, Davide; Rezk, Martin; Xiao, Guohui; Ozcep, Ozgur; Rosati, Riccardo (Computer (00189162), 2015)
Optique overcomes problems in current ontology-based data access systems pertaining to installation overhead, usability, scalability, and scope by integrating a user-oriented query interface, semi-automated managing methods, new query rewriting techniques, and temporal and streaming data processing in one platform.